2014
DOI: 10.1021/sc500034r
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Mediated Synthesis of Ag–Pd Alloy Nanoparticles and Their Application as Catalyst toward Selective Hydrogenation

Abstract: Herein, we reported the green synthesis of Ag–Pd alloy nanoparticles (NPs) using the aqueous extract of the Cacumen platycladi leaves as well as their application as catalyst for hydrogenation of 1,3-butadiene. The biosynthetic NPs were characterized to confirm the nature of alloy by UV–vis spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy (EDX). The possible functional groups responsible for the reduction and protection of NPs were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 49 publications
4
52
0
Order By: Relevance
“…184 The synthesized Au meatball-like NPs possess excellent monodispersity and uniform size (250 nm in diameter). 190 B10 nm AuAg alloy NPs could also be prepared using a similar method. The first example was reported by Huang et al, 185 who described the continuousflow biosynthesis of Ag NPs using Cinnamomum camphora (C. camphora) leaf extract.…”
Section: Plant-mediated Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…184 The synthesized Au meatball-like NPs possess excellent monodispersity and uniform size (250 nm in diameter). 190 B10 nm AuAg alloy NPs could also be prepared using a similar method. The first example was reported by Huang et al, 185 who described the continuousflow biosynthesis of Ag NPs using Cinnamomum camphora (C. camphora) leaf extract.…”
Section: Plant-mediated Synthesismentioning
confidence: 99%
“…187 The model and its applicability in predicting formation and particle size distribution of Ag NPs in the continuous-flow tubular system were subsequently validated. Lu et al 190 reported a facile and green synthesis of AgPd alloy bimetallic NPs using C. Platycladi extract. 188 Besides monometallic NPs, bimetallic NPs could also be simply synthesized by plant-mediated synthesis.…”
Section: Plant-mediated Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The methods impending nanoparticles (NPs) like a chemical, photo-reduction, and thermal decomposition have been limited due to non-eco-friendly and expensive pathways [1][2][3]. Due to increasing hazards using toxic chemicals, capping agents, oxidizing and reducing agents in the synthesis of NPs, researchers have proposed new engineering strategies using the combination of natural resources and nano-biotechnology [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lignin-stabilized PdNPs were successfully used as catalysts in the reduction of 4-nitrophenol to 4-aminophenol and the oxida-tion of cyclohexanol [46]. The bimetallic nanoparticles of Ag/Pd supported on g-Al 2 O 3 created with the help of an aqueous extract of Cacumen platycladi leaves demonstrated excellent catalytic effect towards the selective hydrogenation of 1,3-butadiene [169]. Au/Pd bimetallic nanoparticles with flower-like morphology prepared using Cacumen platycladi leaf extract exhibited excellent surface-enhanced Raman spectroscopic (SERS) activity with rhodamine 6G (R6G).…”
Section: Applications and Emerging Opportunitiesmentioning
confidence: 99%